2016
DOI: 10.1371/journal.pone.0152628
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Hyperactivation by Ablation of Tuberous Sclerosis Complex 2 in the Mouse Heart Induces Cardiac Dysfunction with the Increased Number of Small Mitochondria Mediated through the Down-Regulation of Autophagy

Abstract: Mammalian target of rapamycin complex 1 (mTORC1) is a key regulator of cell growth, proliferation and metabolism. mTORC1 regulates protein synthesis positively and autophagy negatively. Autophagy is a major system to manage bulk degradation and recycling of cytoplasmic components and organelles. Tuberous sclerosis complex (TSC) 1 and 2 form a heterodimeric complex and inactivate Ras homolog enriched in brain, resulting in inhibition of mTORC1. Here, we investigated the effects of hyperactivation of mTORC1 on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 57 publications
2
52
0
1
Order By: Relevance
“…In yeast and mammalian cells, the Ras and mTOR pathways are two well-known signaling cascades that are sensitive to nutrient status, cell growth and differentiation, and are negatively regulated during programmed cell death (34). The phosphoinositide 3-kinase/Akt/mTOR pathway exists in several types of cancer and may be activated by the loss of tumor suppressor phosphatase and tensin homolog (PTEN) function (35).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast and mammalian cells, the Ras and mTOR pathways are two well-known signaling cascades that are sensitive to nutrient status, cell growth and differentiation, and are negatively regulated during programmed cell death (34). The phosphoinositide 3-kinase/Akt/mTOR pathway exists in several types of cancer and may be activated by the loss of tumor suppressor phosphatase and tensin homolog (PTEN) function (35).…”
Section: Discussionmentioning
confidence: 99%
“…CFs were incubated with 3AB (10 μM, 24 hours) or ABT-888 (10 μM, 24 hours) followed by incubation with TGF-β1 (10 ng/mL for 24 hours). [11][12][13][14][15][16][17][18][19][20][21] It is mainly due to the effect of mTOR on collagen expression, Smad3, p53/JNK-mediated F I G U R E 6 Involvement of mTOR in PARP1-mediated cardiac fibrosis in vitro. B and G, The protein levels of PARP1 and mTOR were determined by Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…8 In particular, activated mTORC1 positively regulates protein synthesis by phosphorylating its downstream substrates, such as p70 ribosomal S6 kinase 1 (S6K1), eukaryotic initiation factor 4E-binding protein 1 (4EBP, eIF4Ebinding protein 1), and UNC51like kinase 1 (ULK1). [11][12][13][14][15][16][17][18][19][20][21] It is mainly due to the effect of mTOR on cardiac collagen expression, Smad3, p53/JNK-mediated apoptosis, autophagy, and inflammatory response. [11][12][13][14][15][16][17][18][19][20][21] It is mainly due to the effect of mTOR on cardiac collagen expression, Smad3, p53/JNK-mediated apoptosis, autophagy, and inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We recently reported that autophagy via the tuberous sclerosis complex 2 (TSC2)-mechanistic or mammalian target of rapamycin complex 1 signaling pathway plays an important role in maintenance of cardiac function and mitochondrial quantity and size in the heart using cardiac-specific TSC2-deficient mice. 43 Furthermore, mechanical unloading of the failing human heart by left ventricular assist device support (with a mean duration of 214 days) decreased markers of autophagy. 44 These findings suggest that autophagy is an adaptive mechanism in the failing heart.…”
Section: Sterile Inflammation and The Innate Immunementioning
confidence: 99%